The Effect of Think-Pair-Share Strategy on Student Learning Achievement: English - Akhmad Nuris Hidayat Nuris (JOEY: Journal of English Ibrahimy, 2023)
Think Pair Share was one of the learning models that give students the opportunity to work alone as well as work together. The researcher used a Think-Pair-Share Strategy in the learning process to know the effectiveness of student learning achievement. It used a quantitative method and took 50 students as a sample and used a questionnaire. Then the data was analyzed using the product moment formula.The r of the calculation result is greater than the r of the table, both at the level of significance of 5% and 1%. Thus, the alternative hypothesis (Ha) is accepted, namely the existence of a positive influence between the variables X and Y, while the null hypothesis (Ho) is rejected. So there is an influence between the think pair share learning model on student achievement